Evaluasi Kualitas Website Pemerintah Daerah Menggunakan Metode E-Govqual (Studi Kasus Pemerintah Kabupaten Sumbawa Barat) - Rizkialdy Suja Pratama; Admaja Dwi Herlambang; Mochamad Chandra Saputra (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
The local government website of West Sumbawa Regency is a media owned by government of West Sumbawa Regency to support the information disclosure to the public. But in its implementation, the website has some perceived weakness of its users. This study discusses how the assessment of the website quality based on the point of view of the user, especially the local people. Website quality evaluation can be done using 6 dimensions and 47 attributes of e-Govqual and perform SWOT Analysis to develop strategy recommendations. This study uses quantitative data obtained through questionnaires and qualitative data from interview activities. Questionnaires were conducted on 104 respondents with incidental sampling techniques and interviews were conducted on 2 interviewees from website administrator and 2 interviewees from website user or local people. The result showed that the highest level on Content and Appearance of Information belongs to high category (75.14%), then followed by Ease of Use belongs to high category (74.5%), Reliability belongs to high category (73.04%), Functionality and Interaction belongs to high category (72.4%), Trust belongs to high category (70.94%) and Citizen Support belongs to high category (70.26%). Strategy recommendations that can be formulated based on SWOT Analysis is to improve the technical issues on the website.